THE EFECT OF BAY LEAFT (SYZYGIUM POLYANTHUM) DECOCTION ON URIC ACID LEVEL REDUCTION IN ELDERLY PATIENTS WITH GOUT ARTHRITIS IN SERANG VILLAGE - Sofiyatun Hasanah; Dwi Astuti; Priyatin Sulistyowati (PT. Jurnal Center Indonesia Publisher, 2025)
Background: Elderly individuals are at high risk of experiencing degenerative diseases, one of which is gout arthritis, caused by the accumulation of monosodium urate crystals in the joints due to hyperuricemia. Non-pharmacological therapies such as bay leaf (Syzygium polyanthum), which contains flavonoids, tannins, and essential oils, are believed to naturally reduce uric acid levels. Objective: To determine the effect of bay leaf decoction on reducing uric acid levels in elderly patients with gout arthritis in Serang Village. Method: This research used a descriptive approach with a case study method. The subject was one elderly person with gout arthritis who was given an intervention in the form of bay leaf decoction twice a day for four days. Results: The uric acid level before the intervention was 8.2 mg/dL and after the intervention was 4.2 mg/dL. The reduction of 4 mg/dL indicates that the bay leaf decoction was effective in lowering uric acid levels. Conclusion: Bay leaf decoction affects the reduction of uric acid levels in elderly patients with gout arthritis and can be used as a safe, easy, and affordable nonpharmacological alternative therapy.